MIRRORS OF MEANING: SUPPORTING INSPECTABLE RUNTIME MODELS. - Gjerlufsen, Tony; Ingstrup, Mads; Olsen, Jesper Wolff (Computer (00189162), 2009)
The article features the hierarchical graph (H-graph) data structure and associated programming model designed to actively engage developers in dealing with runtime understandability. It discusses the method's exploration of how to apply runtime models of software to assist inspection by users with various kinds and levels of expertise. The levels of H-graph abstraction and the functions of a data-structure-centered programming model for reflexive systems are also described.